Estimating willingness to pay for parks: Evidence from a developing country - Asia Baig; Zahoor Ul Haq; Javed Iqbal; Muhammad Yusuf Amin (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
This study estimates visitors' willingness to pay (WTP) for the economic, health and social benefits that they get by visiting the public parks. Primary data through a structured questionnaire was collected from 400 respondents using Bagh-i-Naran Park, situated in Hayatabad, Peshawar, Khyber Pakhtunkhwa, Pakistan. Regression results estimated using Logit model show that the cost of visiting public parks, family size, interaction with nature, gender, health issues, and concern for protection & conservation of nature were the key factors that affected WTP for visiting public parks. Contrary to the general observation, income, education and age of the respondents were found statistically insignificant. The study concludes that visitors are willing to pay more as they become more aware about the social, health, economic and environmental benefits of public parks.
Keywords: 330; visits to parks; willingness to pay; contingent valuation method; logit model